Insights into complexation and enantioselectivity of uranyl‐2‐(2‐hydroxy‐3‐methoxyphenyl)‐9‐(2‐hydroxyphenyl)thiopyrano[3,2‐h]thiochromene‐4,7‐dione with R/S‐organophosphorus pesticides - Yang, Rong; Xiao, Yang; Tao, Xue‐bing; Ma, Ming‐jie; Wu, Zhi‐lin; Liao, Li‐fu; Xiao, Xi‐lin; Nie, Chang‐ming (Applied organometallic chemistry, 2021)
In order to explore the enantioselectivity of new uranyl receptors to chiral organophosphorus pesticides (COPs), we designed a novel ligand: 2‐(2‐hydroxy‐3‐methoxyphenyl)‐9‐(2‐hydroxyphenyl)thiopyrano[3,2‐h]thiochromene‐4,7‐dione (HTTDN) and constructed a new receptor of Uranyl‐HTTDN by complexation of HTTDN with uranyl. The complexation and enantioselectivity of Uranyl‐HTTDN to COPs of R/S‐methamidophos (R/S‐MAPs) and R/S‐acephates (R/S‐APs) were studied using density functional theory (DFT) method in this paper. The results showed that in vacuum and toluene, Uranyl‐HTTDN could effectively recognize R/S‐MAPs by complexation with oxygen of phosphoryl of methamidophos, with enatioselectivity coefficients of 91.80% and 86.74%, respectively. In vacuum, water, and acetone, Uranyl‐HTTDN could also effectively identify R/S‐APs by the oxygen of phosphoryl coordinating with U, and enatioselectivity coefficients toward R/S‐APs were 99.41%, 91.09%, and 93.84%, respectively. These results could provide valuable information and theoretical reference for the further experiments of COPs separation. In this paper, we designed a novel ligand: 2‐(2‐hydroxy‐3‐methoxyphenyl)‐9‐(2‐hydroxyphenyl)thiopyrano[3,2‐h]thiochromene‐4,7‐dione (HTTDN) and constructed a new receptor of Uranyl‐HTTDN by complexation of HTTDN with uranyl. Uranyl‐HTTDN could be selectively coordinated with the oxygen of phosphoryl and amino nitrogen of R/S‐methamidophos (R/S‐MAPs) and could also be selectively coordinated with the oxygen of phosphoryl and carbonyl oxygen of R/S‐acephates (R/S‐APs). This work could provide valuable information and theoretical reference for the further experiments of chiral organophosphorus pesticides separation.